Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 142149 by cesarL last updated on 27/May/21

6. ∫(dx/(x^2 −3x+2))  7. ∫((4dx)/(x^2 +2x+4))  8. ∫((3−2xdx)/(x^2 −64))  9. ∫((3x−1)/(x^3 +5x^2 +6x))dx  10. ∫((4−3x)/(x^3 −2x))dx  11. ∫(dx/(x^3 −2x+x))

6.dxx23x+27.4dxx2+2x+48.32xdxx2649.3x1x3+5x2+6xdx10.43xx32xdx11.dxx32x+x

Answered by mathmax by abdo last updated on 27/May/21

1) I=∫ (dx/(x^2 −3x+2))  x^2 −3x+2=0→Δ=9−8=1 ⇒x_1 =((3+1)/2)=2 and x_2 =((3−1)/2)=1 ⇒  I=∫ (dx/((x−2)(x−1)))=∫ ((1/(x−2))−(1/(x−1)))dx=log∣((x−2)/(x−1))∣ +C

1)I=dxx23x+2x23x+2=0Δ=98=1x1=3+12=2andx2=312=1I=dx(x2)(x1)=(1x21x1)dx=logx2x1+C

Answered by mathmax by abdo last updated on 27/May/21

2) J=∫ ((4dx)/(x^2  +2x+4)) ⇒J=∫ ((4dx)/((x+1)^2 +3))  =_(x+1=(√3)y)   ∫  ((4(√3)dy)/(3(y^2 +1))) =(4/( (√3))) arctany +C  =(4/( (√3)))arctan(((x+1)/( (√3)))) +C

2)J=4dxx2+2x+4J=4dx(x+1)2+3=x+1=3y43dy3(y2+1)=43arctany+C=43arctan(x+13)+C

Answered by mathmax by abdo last updated on 27/May/21

3) I=∫ ((−2x+3)/(x^2 −64))dx  F(x)=((−2x+3)/(x^2 −64))=((−2x+3)/((x−8)(x+8)))=(a/(x−8))+(b/(x+8))  a=((−16+3)/(16)) =−((13)/(16))  b=((16+3)/(−16)) =−((19)/(16)) ⇒F(x)=−((13)/(16(x−8)))−((19)/(16(x+8))) ⇒  I=−((13)/(16))log∣x−8∣−((19)/(16))log∣x+8∣ +C

3)I=2x+3x264dxF(x)=2x+3x264=2x+3(x8)(x+8)=ax8+bx+8a=16+316=1316b=16+316=1916F(x)=1316(x8)1916(x+8)I=1316logx81916logx+8+C

Answered by mathmax by abdo last updated on 27/May/21

5) J=∫ ((3x−1)/(x^3  +5x^2 +6x))dx  F(x)=((3x−1)/(x(x^2  +5x+6)))  x^2  +5x+6=0→Δ=25−24=1 ⇒x_1 =((−5+1)/2)=−2  x_2 =((−5−1)/2)=−3 ⇒F(x)=((3x−1)/(x(x+2)(x+3)))=(a/x)+(b/(x+2))+(c/(x+3))  a=−(1/6),b=((−7)/((−2)(1)))=(7/2),c=((−10)/((−3)(−1)))=−((10)/(3 )) ⇒  F(x)=−(1/(6x)) +(7/(2(x+2)))−((10)/(3(x+3))) ⇒J=∫ F(x)dx  =−(1/6)log∣x∣+(7/2)log∣x+2∣−((10)/3)log∣x+3∣ +C

5)J=3x1x3+5x2+6xdxF(x)=3x1x(x2+5x+6)x2+5x+6=0Δ=2524=1x1=5+12=2x2=512=3F(x)=3x1x(x+2)(x+3)=ax+bx+2+cx+3a=16,b=7(2)(1)=72,c=10(3)(1)=103F(x)=16x+72(x+2)103(x+3)J=F(x)dx=16logx+72logx+2103logx+3+C

Answered by Panacea last updated on 27/May/21

Q11.  ∫(dx/(x^3 −2x+x)) = ∫(dx/(x(x+1)(x−1)))    ∫(((−1)/x)+((1/2)/(x+1))+((1/2)/(x−1)))dx  ln(1/x)+(1/2)ln(x^2 −1)  ln((((√(x^2 −1))))/x)

Q11.dxx32x+x=dxx(x+1)(x1)(1x+1/2x+1+1/2x1)dxln1x+12ln(x21)ln(x21)x

Terms of Service

Privacy Policy

Contact: info@tinkutara.com